2022
DOI: 10.1080/00325899.2022.2102839
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mechanical properties and microstructure of Ti-15% Mo alloy produced by mechanical alloying and sintering with SPS (MA-SPS)

Abstract: The goal of this study was to investigate the mechanical properties and microstructure of Ti-15% Mo alloy fabricated using the mechanical alloying and spark plasma sintering (MA-SPS) method. Accordingly, Ti and Mo powders were milled for different times, including 5, 15, 25, 35, and 45 h, and the SPS technique for sintering under a pressure of 25 MPa at 1100°C was used. The X-ray diffraction (XRD) analysis, optical and electron microscopy (SEM), hardness measurements, and compression testing were used to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…15,16,18 Tensile strengths from sub-size test specimens have also been reported; for example, ∼350 MPa with ∼30% elongation for < 45 µm GA grade 1 CP-Ti and ∼600 MPa with ∼15% elongation for < 45 µm angular grade 3 CP-Ti, 19 978-1045 MPa with 6.3-18.2% elongation for < 45 µm GA Ti-6Al-4V, 20 1240 MPa with 19.5% elongation for 75-150 µm GA Ti-6Al-4V through manipulation of FAST load and temperature to create a 'bimorphic' microstructure, 21 844/893 MPa with 12/17% elongation for 53-106 µm GA Ti-6Al-4V either as-FAST or with subsequent heat treatment, 22 and 1183 MPa with 6% elongation for Ti-5Al-5V-5Mo-3Cr created from blended elemental 10-80 µm angular and spherical powders. 23 Several studies have also examined the potential to enhance mechanical properties of titanium alloys by performing extensive milling of the powders prior to FAST consolidation [24][25][26][27][28] ; although it was reported that the fatigue life of both un-milled and milled powders was 74% of the materials' tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…15,16,18 Tensile strengths from sub-size test specimens have also been reported; for example, ∼350 MPa with ∼30% elongation for < 45 µm GA grade 1 CP-Ti and ∼600 MPa with ∼15% elongation for < 45 µm angular grade 3 CP-Ti, 19 978-1045 MPa with 6.3-18.2% elongation for < 45 µm GA Ti-6Al-4V, 20 1240 MPa with 19.5% elongation for 75-150 µm GA Ti-6Al-4V through manipulation of FAST load and temperature to create a 'bimorphic' microstructure, 21 844/893 MPa with 12/17% elongation for 53-106 µm GA Ti-6Al-4V either as-FAST or with subsequent heat treatment, 22 and 1183 MPa with 6% elongation for Ti-5Al-5V-5Mo-3Cr created from blended elemental 10-80 µm angular and spherical powders. 23 Several studies have also examined the potential to enhance mechanical properties of titanium alloys by performing extensive milling of the powders prior to FAST consolidation [24][25][26][27][28] ; although it was reported that the fatigue life of both un-milled and milled powders was 74% of the materials' tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…Ti64 alloy is one of the most important titanium alloys of (a + β) type, which was founded in 1954 with the addition of 6% aluminium to stabilise the α-phase and 4% vanadium to stabilise the β-phase [8]. Owing to the high corrosion resistance, mechanical properties, and good biocompatibility of this alloy, it is not surprising that it is used for various medical applications [6,7,9,10]. Titanium and its alloys have high melting temperatures and it is difficult to inhibit their reaction with atmospheric gases such as oxygen and nitrogen in the liquid state [11].…”
Section: Introductionmentioning
confidence: 99%